PENGELOLAAN SUMBER DAYA ALAM DALAM PERSPEKTIF EKONOMI HIJAU (GREEN ECONOMY) - Gracelino Prasetyo Nainggolan; Jogi Situmorang; Samuel Revaldo Jeverson Siboro; Bonaraja Purba (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The exploitation of natural resources (SDA) that ignores ecological carrying capacity has triggered environmental degradation, climate change, and a decline in the quality of life of communities dependent on natural resources. This article aims to examine natural resource management from the perspective of the green economy, a development paradigm that prioritizes resource efficiency, low-carbon growth, and social inclusiveness. This study uses a literature review method by collecting, analyzing, and synthesizing relevant scientific sources, including journal articles, books, and institutional reports, related to the concepts of green economy and natural resource management. The results of the study indicate that the green economy paradigm offers a strategic framework for reconciling economic growth with environmental sustainability through instruments such as economic valuation of natural resources, green investment, environmental regulation, and community participation. However, its implementation in Indonesia still faces obstacles in the form of overlapping regulations, weak institutional coordination, and limited public understanding of the green economy concept. This article concludes that the success of green economy-based natural resource management requires synergy among the government, the private sector, and the community, supported by a regulatory framework that is consistent and oriented toward sustainable development.